PENERAPAN MESIN PENIRIS MINYAK (SPINNER) UNTUK MENINGKATKAN EFISIENSI PRODUKSI DAN KUALITAS DARI KERUPUK KULIT PADA IKM RIZKY DI KOTA PADANG - Indri Juliyarsi; Sri Melia; Ade Sukma; Rizki Dwi Setiawan; Ahmad Syafruddin Indrapriyatna; Tuty Anggraini (LPPM Universitas Andalas, 2022)
The process of making skin crackers, which is carried out in four stages of frying, results in a high oil content in the product. This is a separate obstacle for business actors in making skin crackers. A high oil content can cause rancidity in the product and requires a long time for oil draining in the production process. IKM partner